2006
DOI: 10.1111/j.1365-2222.2006.02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary role of growth‐related oncogene‐α and granulocyte chemotactic protein‐2 as neutrophil chemoattractants in chronic rhinosinusitis

Abstract: It appears that both GRO-alpha and GCP-2 contribute to neutrophil chemotaxis in CRS, whereas IL-8 and ENA-78 appear to be of secondary importance for the chemotaxis of neutrophils in this condition. The expression of chemokines in mucosal gland cells is the main phenomenon involved in constitutive neutrophil chemotaxis in the TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In CF and CRS patients, CXCL6 was detected in lung epithelium goblet cells and was a more potent neutrophil chemoattractant than CXCL8, while treatment with an anti-CXCL6 antibody reduced neutrophil influx and inflammation in a mouse model of IPF (59)(60)(61)(62)(63). Similarly, CXCR6 was expressed on lung-infiltrating Th2 cells in a mouse model of asthma (62) and in asthmatic patients (61).…”
Section: Secretome Directionality and Homeostatic Processesmentioning
confidence: 99%
“…In CF and CRS patients, CXCL6 was detected in lung epithelium goblet cells and was a more potent neutrophil chemoattractant than CXCL8, while treatment with an anti-CXCL6 antibody reduced neutrophil influx and inflammation in a mouse model of IPF (59)(60)(61)(62)(63). Similarly, CXCR6 was expressed on lung-infiltrating Th2 cells in a mouse model of asthma (62) and in asthmatic patients (61).…”
Section: Secretome Directionality and Homeostatic Processesmentioning
confidence: 99%
“…52 In states of chronic inflammation such as inflammatory bowel disease (characterized by unremitting leukocyte infiltration in affected tissues), CXCL6 expression is selectively up-regulated in endothelial cells at sites of intestinal inflammation and ulceration. 34 Furthermore, Rudack et al 53 describe the pattern of chemokine expression in patients with chronic rhinosinusitis, a neutrophilmediated condition. CXCL6 and GRO-a were the pre-dominant chemokines produced by affected mucosa and epithelial cells.…”
Section: Cxcl6 In Pathologic Conditionsmentioning
confidence: 99%
“…Regarding the inflammation, accumulating evidence has shown that chemokine levels play important roles in the progression of airway inflammation [ 11 – 12 ]. Among these chemokines, the CXC chemokines such as CXCL1 and CXCL8, are primarily chemotactic factors for leukocytes and are potent promoters of angiogenesis and tissue inflammation [ 13 14 ]. CXCL1 and -8 can bind their receptors, including CXCR1 and -2 [ 15 ] and direct the migration of circulating leukocytes to sites of inflammation or injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%